Pharmacogenomics and Personalized Medicine in Type 2 Diabetes - Yudhani, Ratih Dewi (PT. Kalbe Farma Tbk., 2015)
Type 2 diabetes has reached epidemic proportions worldwide and poses a considerable concern for public health. Although a variety of pharmacological treatments is available, response, doses and tolerability to drugs are highly variable and monotherapy often failed. A large interindividual variability in drug response has been noticed and contributing factors include age, sex, disease, drug and food interactions, comorbidity, as well as genetic factors. Poor therapeutic outcomes may be caused by variability of individual characteristics.Personalized medicine is an emerging concept for treating diseases, which involves determining specific information of a particular patient and then prescribing specific treatment. Pharmacogenetics holds the promise of bringing personalized medicine to drug dosing decisions, to reduce morbidity and mortality, and to improve life quality for T2DM patients.Diabetes Mellitus tipe 2 telah merupakan epidemi di seluruh dunia dan menjadi perhatian besar di bidang kesehatan. Meskipun berbagai terapi farmakologis telah tersedia, namun respon, dosis dan tolerabilitas penderita sangat bervariasi dan monoterapi sering gagal. Terdapat variabilitas besar terkait respon terapi diantara individu dan beberapa faktor yang berperandiantaranya usia, jenis kelamin, penyakit, interaksi obat dengan makanan, komorbiditas, serta faktor genetik. Variabilitas besar terkait respon terapi obat hipoglikemik sering dijumpai di klinik. Respon terapi tidak optimal mungkin karena pemilihan terapi tanpa memperhatikan karakteristik individual. Personalized medicine merupakan konsep terkini pemberian terapi. Pada konsep ini, pemilihan jenis terapi mempertimbangkan profil genetik maupun karakteristik individual. Farmakogenetik menjadi kunci mewujudkan personalized medicine sehingga diharapkan dapat mengurangi morbiditas dan mortalitas penyakit, serta meningkatkan kualitas hidup penderita Diabetes Mellitus Tipe 2.